Silicified termite coprolites in mesquite-like wood from the Miocene of La Rioja, Argentina - García Massini, Juan Leandro (2013)
Coprolite-filled borings in fragments of non-decayed wood showing affinity with the mesquite-like morphogenus Prosopisinoxylon Martinez are described from Miocene strata from La Rioja, northwestern Argentina. Borings are excavated in the secondary xylem and contain numerous cylindrical coprolites with a characteristic hexagonal shape in cross section. Coprolites are rather inconspicuous and only visible through the exposed ends of the borings. The concealed occurrence of the coprolites inside the borings, the non-decayed state of the mesquite-like wood and the overall morphology of the fossils suggest dry-wood members of the termite family (Kalotermitidae), as a probable producer. This is the first fossil record of termites from northwestern Argentina and is among the few known from South America, thereby expanding their paleobiogeographic range. The presence of dry-wood termites in the studied deposits is consistent with a forested environment set in an arid tropical to subtropical climate. In this setting termites probably had a significant role in the recycling of organic matter. Their association with mesquite-like wood suggests that the current relationship between termites and members of this genus in modern ecosystems dates back to at least the Late Miocene.